Exchange Rate Uncertainty and International Portfolio Flows - Guglielmo Maria Caporale; Faek Menla Ali; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper examines the impact of exchange rate uncertainty on different components of portfolio flows, namely equity and bond flows, as well as the dynamic linkages between exchange rate volatility and the variability of these two types of flows. Specifically, a bivariate GARCH-BEKK-in-mean model is estimated using bilateral data for the US vis-à-vis Australia, the UK, Japan, Canada, the euro area, and Sweden over the period 1988:01-2011:12. The results indicate that the effect of exchange rate uncertainty on equity flows is negative in the euro area, the UK and Sweden, and positive in Australia, whilst it is negative in all countries except Canada (where it is positive) in the case of bond flows. Under the assumption of risk aversion, this suggests that exchange rate uncertainty induces a home bias and causes investors to reduce their financing activities to maximise returns and minimize exposure to uncertainty. Furthermore, since exchange rate volatility and the variability of flows are interlinked, exchange rate or credit controls on these flows can be used to pursue economic and financial stability.
Keywords: F31; F32; G15; 330; exchange rate uncertainty; equity flows; bond flows; causality-in-variance